AB0982 Dichotomous Scoring of Ra Ultrasound Inflammation Demonstrates Good Responsiveness Compared To Semi-Quantitative Scoring When Using Novel Joint Selection Methods. (15th July 2016) - Tan, Y.K.; Allen, J.C.; Lye, W.K.; Conaghan, P.G.; Chew, L.C.; Thumboo, J.
Abstract : Background: Novel joint selection methods using semi-quantitative scoring (SQS) of ultrasound (US) joint inflammation (power Doppler (PD) vascularity and grey-scale synovial hypertrophy (GSSH)) have shown good sensitivity to change versus existing methods and DAS28 in RA (1). However SQS may have more variability than dichotomous scoring (DS) as SQS requires grading across multiple categories. Objectives: Compare responsiveness of DS of US joint inflammation versus SQS using 2 novel and 2 existing joint selection methods. Methods: Novel methods were Individualized US [IUS], which selects up to 7 or 12 most inflamed joints on US and Individualized Composite-US [ICUS], which additionally considers joint symptoms. Existing methods were a pre-defined 7-joint count and a 12-joint count derived from an US data reduction method. PD vascularity and GSSH at the joints were scored via a DS system [USDSS] as Y/N or via a SQS system [USSQS] on a 0–3 severity scale. Both systems scored tenosynovitis (PD and GS changes), tender and swollen joints as Y/N. Joint pain was scored as Y/N (with USDSS) or using a 0–3 severity scale (with USSQS). Responsiveness at 3 months was measured using the standardized response mean (SRM). Relative gains in SRM magnitude (SRM-Gains) were reported comparing novel to existing methods. Results: 20 RA subjects (mean DAS28 at baseline and 3-months =4.68 and 4.19, respectively) starting/escalating on DMARDs and corticosteroid therapy were followed for 3 months. SRMs using existing methods were modest for both USDSS and USSQS (ranged from 0.30 to 0.49). SRMs ranged from 0.94 to 1.06 using novel methods with both systems. There were substantial SRM-Gains (ranged from 1.94 to 3.47) for both systems using ICUS and IUS with the 7 or 12 joint approaches. Conclusions: Results of this small study suggest USDSS may be as responsive as USSQS (both had substantial SRM-Gains) using novel joint selection methods. References: Tan YK et al. J Rheumatol. 2016;43(1):34–7 Acknowledgement: NCS grant and Estate of Tan Sri Khoo Teck Puat for funding support and the NUS Disclosure of Interest: None declared